Quantum cutting effect and photoluminescence emission at about 1,000 nm from Er-Yb co-doped ZnO nanoplates prepared by wet chemical precipitation method - Zamiri, Reza
ZnO nanoplates with Er-doping concentrations varying in the range from 3 to 7 wt% and co-doped with (Er-Yb) (7 x 7 wt%) were successfully prepared by wet chemical precipitation method. The effects of doping on the structural and optical properties of ZnO nanostructures have been systematically investigated. The structural morphology of the prepared nanostructures was found to change with increasing Er-doping concentrations. The visible photoluminescence and infrared photoluminescence of the prepared nanostructures were measured at room temperature. The intensity of visible emission spectra was found to increase with increasing Er-doping concentrations and was further enhanced for (Er-Yb) co-doped ZnO nanoplate samples. Additionally, Er-doped (7 wt%) and Yb-doped (7 wt%) ZnO nanoplates showed an enhanced emission peak at 950 nm, whereas two enhanced emission peaks at 950 and 980 nm have been found for (Er-Yb)-co-doped (7 x 7 wt%) ZnO nanoplates samples when excited at 310, 365 and 371 nm excitation wavelengths.